Abandon the coat Experiential group about clinical psychologist’s identity - Maria Caterina Branca; Emanuela Coppola; Eleonora Schinella (Mediterranean Journal of Clinical Psychology, 2014)
This research was driven by the fundamental idea that one of the main methodological competencies of a psychologist is to be able to think one’s emotions (especially those formed within a relationship) and to use them to build theories on the relationship itself. In this context, the project aims to explore the role identity of the trainee psychologist, that is to say the mental representations (fantasies, subconscious associations, myths) of those who have just finished their university journey and are about to embark upon the world of work in the field of applied clinical psychology.